Dimethylallyl Diphosphate and Geranyl Diphosphate Pools of Plant Species Characterized by Different Isoprenoid Emissions - Nogués, Isabel (American Society of Plant Biologists, 2006)
Dimethylallyl diphosphate (DMADP) and geranyl diphosphate (GDP) are the last precursors of isoprene and monoterpenes emitted by leaves, respectively. DMADP and GDP pools were measured in leaves of plants emitting isoprene (Populus alba), monoterpenes (Quercus ilex and Mentha piperita), or nonemitting isoprenoids (Prunus persica). Detectable pools were found in all plant species, but P. persica showed the lowest pool size, which indicates a limitation of the whole pathway leading to isoprenoid biosynthesis in nonemitting species. The pools of DMADP and GDP of nonemitting, isoprene-emitting, and monoterpene-emitting species were partially labeled (generally 40%–60% of total carbon-incorporated (13)C) within the same time by which volatile isoprenoids are fully labeled (15 min). This indicates the coexistence of two pools for both precursors, the rapidly labeled pool presumably occurring in chloroplasts and thereby synthesized by the methylerythritol phosphate pathway and the nonlabeled pool presumably located in the cytosol and synthesized by the mevalonic pathway. In M. piperita storing monoterpenes in specialized leaf structures, the GDP pool remained totally unlabeled, indicating either that monoterpenes are totally formed by the mevalonic pathway or that labeling occurs slowly in comparison to the large pool of stored monoterpenes in this plant. The pools of DMADP and GDP increased during the season (from May to July) but decreased when the leaf was darkened or exposed to very high temperature. In the dark, the pool of DMADP of the isoprene-emitting species decreased faster than the pool of GDP. However, after 6 h of darkness, both pools were depleted to about 10% of the pool size in illuminated leaves. This indicates that both the chloroplastic and the cytosolic pools of precursors are depleted in the dark. When comparing measurements over the season and at different temperatures, an inverse correlation was observed between isoprene emission by P. alba and the DMADP pool size and between monoterpene emission by Q. ilex and the GDP pool size. This suggests that the pool size does not limit the emission of isoprenoids. Rather, it indicates that the flux of volatile isoprenoids effectively controls the size of their pools of precursors.